2020
DOI: 10.1016/j.mechatronics.2020.102427
|View full text |Cite
|
Sign up to set email alerts
|

Toward observable UHVCVD: Modeling of flow dynamics and AAS partial pressure measurement implementation

Abstract: Ultra-high vacuum chemical vapor deposition is a thin film deposition process that features excellent film purity, but is sensitive to the processing variations (such as, the precursors and their dispensers, the reactor's initial condition, etc.). In this paper, we present the design of a ultra-high vacuum chemical vapor deposition reactor with in-situ partial pressure atomic absorption spectroscopy measurement that improves reproducibility and observability of such a process. Our main contributions are: (i). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In UHV‐CVD method, the reactor pressure is kept at extremely low levels to achieve high purity, especially when the precursors can react and generate a binding with the residual gasses. This process is often performed at lower temperatures compared to the conventional CVD techniques, in order to decrease the chance of dopant evaporation 87 . It should be noted that after dopant evaporation, which can happen at high temperatures, it is possible for the evaporated species to return to the surface and change the concentration of dopant.…”
Section: Cvd Techniques For the Modification Of Thin Films And Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…In UHV‐CVD method, the reactor pressure is kept at extremely low levels to achieve high purity, especially when the precursors can react and generate a binding with the residual gasses. This process is often performed at lower temperatures compared to the conventional CVD techniques, in order to decrease the chance of dopant evaporation 87 . It should be noted that after dopant evaporation, which can happen at high temperatures, it is possible for the evaporated species to return to the surface and change the concentration of dopant.…”
Section: Cvd Techniques For the Modification Of Thin Films And Membranesmentioning
confidence: 99%
“…This process is often performed at lower temperatures compared to the conventional CVD techniques, in order to decrease the chance of dopant evaporation. 87 It should be noted that after dopant evaporation, which can happen at high temperatures, it is possible for the evaporated species to return to the surface and change the concentration of dopant. In a recent study, Byeon et al well demonstrated the advantageous features of using UHV-CVD compared to LP-CVD for the epitaxial growth of Si and SiGe in the absence of a carrier gas.…”
Section: Ultrahigh Vacuum Cvdmentioning
confidence: 99%